Association between SARS-CoV-2 infection and anti-apolipoprotein A-1 antibody in children - Vuilleumier, Nicolas; Pagano, Sabrina; Lorthe, Elsa; Lamour, Julien; Nehme, Mayssam; Juillard, Catherine; Barbe, Remy; Posfay-Barbe, Klara M.; Guessous, Idris; Stringhini, Silvia; , SEROCoV-KIDS study group; L’Huillier, Arnaud G. (Frontiers in Immunology, 2025)
Background and aimsAutoantibodies against apolipoprotein A-1 (AAA1) are elicited by SARS-CoV-2 infection and predict COVID-19 symptoms persistence at one year in adults, but whether this applies to children is unknown. We studied the association of SARS-CoV-2 exposure with AAA1 prevalence in children and the association of AAA1 seropositivity with symptom persistence.MethodsAnti-SARS-CoV-2 and AAA1 serologies were examined in 1031 participants aged 6 months to 17 years old from the prospective SEROCOV-KIDS cohort and recruited between 12.2021 and 02.2022. Four SARS-CoV-2 serology-based groups were defined: “Infected-unvaccinated (I+/V-)”, “Uninfected-vaccinated (I-/V+)”, “Infected-Vaccinated (I+/V+)”, and “Naïve (I-/V-)”. Reported outcomes were collected using online questionnaires. Associations with study endpoints were assessed using logistic regression.ResultsOverall, seropositivity rates for anti-RBD, anti-N, and AAA1 were 71% (736/1031), 55% (568/1031), and 5.8% (60/1031), respectively. AAA1 showed an inverse association with age but not with any other characteristics. The I+/V- group displayed higher median AAA1 levels and seropositivity (7.9%) compared to the other groups (p ≤ 0.011), translating into a 2-fold increased AAA1 seroconversion risk (Odds ratio [OR]: 2.11, [95% Confidence Interval (CI)]: 1.22-3.65; p=0.008), unchanged after adjustment for age and sex. AAA1 seropositivity was independently associated with a 2-fold odds of symptoms persistence at ≥ 4 weeks (p ≤ 0.03) in the entire dataset and infected individuals, but not ≥ 12 weeks.ConclusionsDespite the limitations of the study (cross-sectional design, patient-related outcomes using validated questionnaires), the results indicate that SARS-CoV-2 infection could elicit an AAA1 response in children, which could be independently associated with short-time symptoms persistence.